Fabrication of highly efficient nano-composite films based on ZnO-g-C3N4 @ PAA-g-(HEC/PVA)-Fe3+ for removal of methylene blue dye from water. (August 2021) - Sultan, Maha; Mansor, Eman S.; Nagieb, Zenat Adeeb; Elsayed, Hamed
Abstract: A physically cross-linked polyacrylic acid-grafted hydroxyethyl cellulose and polyvinyl alcohol [PAA-g-(HEC-PVA)]–Fe 3+ containing graphitic-like carbon nitride (ZnO-g-C3 N4 ) was constructed to enhance the adsorption capacity of methylene blue dye (MB). The ZnO-g-C3 N4 and the grafts were investigated by TEM, ART-IR, XRD and SEM. Swelling properties showed reasonable responses to physical crooslinker (FeCl3 ), ZnO-g-C3 N4 contents and pH. The ZnO-g-C3 N4 (6%)@PAA-g-(HEC/PVA)-Fe 3+ has higher swelling ratio (13.18 ± 0.51 g/g) after 6 h. However, it exhibited declined swelling ratio (5.86 ± 0.32 and 7.49 ± 0.42 g/g) at lower pH 3.0 and 5.0, respectively, and (13.48 ± 0.42 and 14.51 ± 0.42 g/g) at pH 9.0 and 11.0, respectively. The swelling data were well-fitted with pseudo-second-order model. The ZnO-g-C3 N4 (6%)@PAA-g-(HEC/PVA)-Fe 3+ has the higher compressive strength (4.74 ± 0.09 MPa) and lower compressive strain (33.78 ± 1.54%). MB adsorbed completely by ZnO-g-C3 N4 (6%)@PAA-g-(HEC/PVA)-Fe 3+ given 100 ± 2.06% up to 50 min at dose 3 g/L for 30 mg/L of MB at pH 9. The ZnO-g-C3 N4 (6%)@PAA-g-(HEC/PVA)-Fe 3+ exhibited 100 ± 2.3% adsorption efficiency (qt ) at dose (300 mg/100 mL). ZnO-g-C3 N4 (6%)@PAA-g-(HEC/PVA)-Fe 3+ exposed the higher adsorption capacity (qt ) 325.42 ± 13.23 mg/g at MB concentration (30 mg/L). The optimum qt by ZnO-g-C3 N4 (6%)@PAA-g-(HEC/PVA)-Fe 3+ at pH (9.0) was (216.82 ± 6.41 mg/g) up to 50 min, however, it was (127.70 ± 5.5 mg/g) at pH 3.0. The adsorption results by ZnO-g-C3 N4 (6%)@PAA-g-(HEC/PVA)-Fe 3+ were fitting with the pseudo-second-order kinetic model. The Langmuir adsorption isotherm exposed the more applicability than Freundlich and Temkin models.